2020
DOI: 10.15575/biodjati.v5i1.7768
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Pelagic and Demersal Fishes of Pantai Baron, Yogyakarta, Indonesia

Abstract: Yogyakarta is the second-largest producer of plastic waste in Indonesia. Plastic waste in the waters can be degraded into microplastics that can enter the body of a fish. This study aimed to determine the presence of microplastics in the digestive tract of several species of fish in Pantai Baron, Yogyakarta, Indonesia. This research was an exploratory research conducted in April-September 2019 at Pantai Baron, Yogyakarta. Two species of each pelagic and demersal fish samples were taken by buying fish caught by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
(54 reference statements)
0
17
0
1
Order By: Relevance
“…In Pangandaran Bay was found 193 microplastic particles in 18 individual fish [15]. The different results were also found in the fish observed at Pantai Baron, Yogyakarta, the total microplastic in 78 fish was 3651 particles [16]. In other tropical country, previous study on 116 marine fish observed in the Gulf of Mexico also reported that 12 individuals were detected having 10.4% of microplastics [17].…”
Section: Discussionmentioning
confidence: 92%
“…In Pangandaran Bay was found 193 microplastic particles in 18 individual fish [15]. The different results were also found in the fish observed at Pantai Baron, Yogyakarta, the total microplastic in 78 fish was 3651 particles [16]. In other tropical country, previous study on 116 marine fish observed in the Gulf of Mexico also reported that 12 individuals were detected having 10.4% of microplastics [17].…”
Section: Discussionmentioning
confidence: 92%
“…Demersal and benthopelagic fishes tend to inhabit areas closer to the seabed, where MPs are more likely to accumulate due to their buoyancy and the effects of ocean currents. These fishes often feed on or near the seafloor and are susceptible to contamination from the sediment, increasing their exposure to MPs that have settled in these habitats (Suwartiningsih et al, 2020). These fishes are also part of complex marine food chains where MPs can accumulate and magnify in concentration as they are consumed by smaller organisms and subsequently passed on to larger predatory fish.…”
Section: Resultsmentioning
confidence: 99%
“…41 Still on Central Java, there are 5 main rivers in Yogyakarta which ferries plastic waste from densely populated area to the sea in southern Yogyakarta, for example, is on Baron Beach, Gunungkidul Regency. 42 On the western area of Java, which is the Banten Gulf, plastic waste are spread through water flow and food chain and then reaching the island chain of Seribu. 43 The beach and rivers were the most specific places of studies.…”
Section: Study Locationmentioning
confidence: 99%
“…Indonesia is known as a dense populated country which certainly affects the abundance of microplastics. 42,65 The total plastic waste generation in Indonesia reaches 5.4 tons per year, which is 14% of the total amount of household waste. 66 Apart from household activities, the presence of microplastics is also influenced by tourism and fishing activities.…”
Section: Study Locationmentioning
confidence: 99%